2017
DOI: 10.26795/2307-1281-2017-3-11
|View full text |Cite
|
Sign up to set email alerts
|

On Some Problems and Tendencies of Development of Educational Organizations of Higher Education and the Regional Resource Centers, Higher Education, Training of Persons With Special Needs and Disabilities on the Results of Monitoring

Abstract: Аннотация. Статья отражает актуальную статистику о деятельности региональных ресурсных центров и образовательных организаций высшего образования, осуществляющих обучение лиц с ОВЗ и инвалидностью, полученную в ходе мониторинга. Одновременно с этим сформулированы исчерпывающие выводы о результатах апробации мониторинговых форм, которые были смоделированы и обсуждались профессиональным сообществом. Приведены примеры количественных данных и аналитических выводов по наиболее значимым показателям мониторинговых дан… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, in modern researches the questions of target orientations in the organization of psychological and pedagogical support of University students are actualized, some organizational and methodical approaches to its realization are presented. At the same time, there is no model of psychological and pedagogical support of students with the inclusion of all subjects of the educational process, there are no approaches to its implementation in relation to persons with disabilities and disabilities (1,4,5,7,8,13,16,17).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, in modern researches the questions of target orientations in the organization of psychological and pedagogical support of University students are actualized, some organizational and methodical approaches to its realization are presented. At the same time, there is no model of psychological and pedagogical support of students with the inclusion of all subjects of the educational process, there are no approaches to its implementation in relation to persons with disabilities and disabilities (1,4,5,7,8,13,16,17).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, in modern researches the questions of target orientations in the organization of psychological and pedagogical support of University students are actualized, some organizational and methodical approaches to its realization are presented. At the same time, there is no model of psychological and pedagogical support of students with the inclusion of all subjects of the educational process, there are no approaches to its implementation in relation to persons with disabilities and disabilities (1,4,5,7,8,13,16,17).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, there are only partial and essentially pilot studies of individual aspects of the identified problem. Employees of the 16 resource educational and methodological centers for the inclusive higher education of disabled people operating in Russia publish separate articles, which usually contain monitoring studies (ZAIR-BEK; BELIKOV; SERGEEV, 2016; KASHTANOVA; KUDRYAVTSEV, 2017;KASHTANOVA, 2016;ROKOTYANSKAYA, 2015;FEDOROV et al, 2018). It is pointed out that the education of disabled people in higher education establishments is now largely spontaneous, without a solid theoretical basis (SELIVANOVA; SHCHETININA, 2017).…”
Section: Introduction To the Problemmentioning
confidence: 99%